THE CLASSIFICATION OF AFFIXES AND THEIR BASIC PECULIARITIES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article "The Classification of Affixes and Their Basic Peculiarities" delves into the intricate world of language morphology, focusing on the pivotal role played by affixes. The comprehensive exploration begins with a clear definition of affixes, emphasizing their transformative nature when added to base words. The article systematically navigates through the classification of affixes, categorizing them based on function and position within a word. The distinction between derivational and inflectional affixes provides a foundational understanding of how affixes contribute to both semantic shifts and grammatical nuances. The section on the basic peculiarities of affixes adds depth to the exploration, touching on productivity, allomorphy, compatibility, and ambiguity. The notion of productivity underscores the dynamic nature of language, showcasing how certain affixes are prolific in generating new words. Allomorphy sheds light on the nuanced variations that affixes can undergo based on their phonological environment, adding a layer of complexity to morphological analysis. The article also recognizes the significance of compatibility, elucidating that not all affixes seamlessly attach to any base word. This highlights the intricate rules governing the formation of words and contributes to a nuanced understanding of morphological structures. Moreover, the acknowledgment of ambiguity underscores the versatility of affixes, which can sometimes convey multiple meanings within different linguistic contexts.